Apelin/APJ system: A bifunctional target for cardiac hypertrophy. (1st March 2017) - Lu, Liqun; Wu, Di; Li, Lanfang; Chen, Linxi
Abstract: Apelin acts as the endogenous ligand of G protein coupled receptors APJ. The apelin/APJ system is responsible for the occurrence and development of cardiovascular diseases. In recent years, apelin/APJ has been considered to play an important role in cardiac hypertrophy, but whether that role is beneficial or aggravating remains controversial. Apelin/APJ alleviates cardiac hypertrophy which is triggered by angiotensin II, oxidative stress and exercise. However, central administration of apelin induces cardiac hypertrophy. Peripheral administration of apelin also promotes the development of cardiac hypertrophy under non-pathological conditions. Furthermore, our laboratory discovers that apelin/APJ is able to induce hypertrophy of cardiomyocytes in vitro. The exact mechanism of apelin/APJ's dual effects in cardiac hypertrophy requires further study. In this paper, we review the controversies associated with apelin/APJ in cardiac hypertrophy and we elaborate the role of apelin/APJ in cardiac hypertrophy related-diseases including obesity, diabetes, hypertension, myocarditis and myocardial infarction. We conclude that further studies should emphasize more about the relationship between apelin/APJ and pathological hypertrophy especially in clinical patients. Moreover, apelin/APJ can be a promising therapeutic target for cardiac hypertrophy. Highlights: Apelin/APJ alleviates cardiac hypertrophy triggered by AngII, H2 O2 and exercise. Central administration of apelin can induce cardiac hypertrophy. Peripheral administration of apelin is likely to promote cardiac hypertrophy. Apelin/APJ system is involved in cardiac hypertrophy related-diseases.